Mix research methods: teaching and learning in 2nd year bachelor nursing program - Ismaile, Samantha; Alsahlia, Haya; Khan, Samina; Alshehri, Hanan (International Journal of Advanced Nursing Studies, 2016)
Background: Nursing profession and its development, no doubt plays a crucial role in healthcare sectors. Students’ learning approaches are now being recognized across higher education as having a considerable effect on student achievement’ and their learning outcomes. The learning process in nursing education has always been a challenge to find pedagogical instructional methods that can engage learners actively and help the students to understand concepts for new applications in theoretical and practical situation.Purpose: The aim of this research study is to compare the effect of sequencing theory via classroom lecturing before practical clinical skill taught in laboratories and visa versa on students learning readiness and approaches.Methods: The research method of this study employed a mixed research methods by the implication of both quantitative and qualitative methods. The quantitative research method was conducted by means of two validated questionnaires. The first questionnaire used is the Self- Directed Learning Readiness Scale for Nursing Education (SDLRSNE). This is a self-reporting instrument designed to assess stu-dents' attitudes, abilities, and personality characteristics necessary for self- directed learning. The second questionnaire is the Revised two-factor version of the Study Process (R-SPQ-2F) in order to assess students’ deep or surface learning approaches. The qualitative research was conducted via students reflection on their learning experience via the use of free text comments in Blackboard Learning Management System (LMS) environment. The study sample included 97 nursing students. Students were divided into two groups A and B. Each group consisted of 47 nursing students.Results: Significant differences between group ‘A’ and group ‘B’ were found for SDLRSNE self-management, desire for learning and self-control, suggesting that self-management in group ‘A’ managed their learning better than group ‘B’. There were no significant differences in terms of learning approaches between group ‘A’ and B.Conclusion: This study highlights that students teaching and learning experiences are sensitive to learning environments. This was done through sequencing theoretical and clinical teaching and visa versa in a nursing course. Proper design of the learning environment and the availability of supportive learning tools encourage students learning and teaching experience.